Antibacterial and Antioxidant Activity of Endophytic Fungi Extract Isolated from Leaves of Sungkai (Peronema canescens) - Rian Oktiansyah; Hary Widjajanti; Arum Setiawan; Sakinah Salman Ahmad Nasution; Mardiyanto; Elfita Elfita (Science and Technology Indonesia, 2023)
Sungkai is a plant that is widely found in Indonesia. This plant is often used in traditional medicine so the biotechnology of endophytic fungi is highly needed due to natural resources from plants that have been reduced. This study reported on endophytic fungi found in sungkai leaves and the compound produced. Morphological and molecular identification through phylogenetic tree analysis was carried out to determine the endophytic fungal species found. Potato Dextrose Broth media was used for the cultivation process. Ethyl acetate was used as a solvent for the extraction and the evaporation process used a rotary evaporator. Antioxidant and antibacterial tests were carried out using the DPPH method and paper disc diffusion. Chromatographic techniques were used to isolate the compound and spectroscopic analysis was performed to identify its chemical structure. The results of the morphological and molecular analysis showed Trichoderma asperellum as an endophytic fungus identified. The pure compound obtained from this endophytic fungus was 4-hydroxybenzoic acid. The antioxidant and antibacterial activity showed a strong category (IC50 = 43.88 ????g/mL; MIC 64 ????g/mL). This compound was very likely to be a raw material for new antibiotics and antioxidants through further research with various modifications.